THE INFLUENCE OF ACTUATING AND CONTROLLING ON THE PERFORMANCE OF THE PROVINCIAL SPORTS WEEK COMMITTEE (PORPROV) XII SUMSEL THE BRANCH OF SOCCER SPORTS IN PRABUMULIHIN 2019 - Fifin Sunarlie; Agustina Hanafi; Iyakrus Iyakrus; Badia Perizade (President University, 2020)
This study aims to determine and analyze the effect of actuating and controlling on the performance of the South Sumatra Province Porprov XII organizing committee in Prabumulih in 2019. The data used in this study are primary data by distributing questionnaires to 128 respondents. The analysis technique used is linear regression analysis. Based on the results of this study, using SPSS version 23 shows that: (1) Actuating has a positive and significant effect on the performance of the Porprov committee. (2) Controlling has a positive and significant effect on the performance of the Porprov committee. The percentage value of the coefficient of determination (R Square) of 0.524 illustrates that 52.4% of the variation in performance variables can be explained by the actuating and controlling variables at Porprov XII South Sumatra Football Branch in Prabumulih in 2019, while 47.6% others are explained by causes other than the model under study. Keywords : Actuating, Controlling, Performance, Porprov, Football